An Association between EMX2 Variations and Mayer-Rokitansky-Küster-Hauser Syndrome: A Case-Control Study of Chinese Women. (13th April 2022) - Li, Haiping; Liao, Shi; Luo, Guangnan; Li, Haixia; Wang, Shuai; Li, Zhimin; Luo, Xiping
Abstract : Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is characterized by congenital malformations of Müllerian structures, including the uterus and upper two-thirds of the vagina in women. Until now, the etiology of this disease has remained unknown. We hypothesized that EMX2 (the human homologue of Drosophila empty spiracles gene (2) might be a candidate gene for MRKH syndrome because it plays an important role in the development of the urogenital system. Through sequence analysis of EMX2 in forty patients with MRKH syndrome and one hundred and forty healthy women controls, we identified eleven variations in total. Four novel variations were only found in MRKH patients, and seven single nucleotide polymorphisms were identified in both patients and controls. In silico analyses suggested that the novel variations in the 5′UTR (untranslated region) and 3′UTR might affect transcriptional activity of the EMX2 promoter or posttranscriptional processing. In conclusion, our study suggests an association between noncoding variations in the EMX2 gene and MRKH syndrome in a Chinese Han population.